A Pseudo‐Vertical Equilibrium Model for Slow Gravity Drainage Dynamics. Issue 12 (14th December 2017) - Becker, Beatrix; Guo, Bo; Bandilla, Karl; Celia, Michael A.; Flemisch, Bernd; Helmig, Rainer
Abstract: Vertical equilibrium (VE) models are computationally efficient and have been widely used for modeling fluid migration in the subsurface. However, they rely on the assumption of instant gravity segregation of the two fluid phases which may not be valid especially for systems that have very slow drainage at low wetting phase saturations. In these cases, the time scale for the wetting phase to reach vertical equilibrium can be several orders of magnitude larger than the time scale of interest, rendering conventional VE models unsuitable. Here we present a pseudo‐VE model that relaxes the assumption of instant segregation of the two fluid phases by applying a pseudo‐residual saturation inside the plume of the injected fluid that declines over time due to slow vertical drainage. This pseudo‐VE model is cast in a multiscale framework for vertically integrated models with the vertical drainage solved as a fine‐scale problem. Two types of fine‐scale models are developed for the vertical drainage, which lead to two pseudo‐VE models. Comparisons with a conventional VE model and a full multidimensional model show that the pseudo‐VE models have much wider applicability than the conventional VE model while maintaining the computational benefit of the conventional VE model. Key Points: Extend vertical equilibrium models for slow gravity drainage Formulate the model in a multiscale framework Maintain the computational efficiency of vertical equilibrium models